WEBALLTED: INTERDISCIPLINARY MODELING IN GRID AND CLOUD - Zgurovsky, Michael; Petrenko, Anatolii; Ladogubets, Volodymyr; Finogenov, Oleksii; Bulakh, Bogdan (Computer Science, 2013)
This paper presents a multi-layered architecture of computer simulation soft-ware capable of utilizing grid and cloud resources, characterized in that thefunctionality of the system is distributed according to a service-oriented ap-proach, and the system supports the execution of custom user-deﬁned com-puting scenarios in grid or in cloud (by web services orchestration with anadherence to existing standards) but hides the complexity of direct web ser-vices management from the user with the help of the abstract workﬂow modeland a web-accessible problem solving environment with a graphical workﬂoweditor.